Zwitterionic silica nanogel-modified polysulfone nanoporous membranes formed by in-situ method for water treatment. (October 2021) - Li, Xiaojiao; Nayak, Kanupriya; Stamm, Manfred; Tripathi, Bijay P.
Abstract: We report a simple methodology to prepare nano-porous polysulfone membranes using zwitterionic functionalized silica nanogels with high BSA protein rejection and antifouling properties. The zwitterionic silica precursor was prepared by reacting 1, 3-propane sultone with 3-aminopropyl triethoxysilane under an inert atmosphere. The precursor was in situ hydrolyzed and condensed in the polysulfone nanoporous membrane network by one-pot acidic phase inversion. The prepared membranes were characterized to establish their physicochemical nature, morphology, and basic membrane properties such as permeation, rejection, and recovery. The zwitterionic membranes showed improved hydrophilicity, membrane water uptake (∼83.5%), water permeation, BSA protein rejection (>95%), and dye rejection (congo red: >52% (∼6-fold increase); methylene blue: ∼15% (∼2-fold increase)) were improved without compromising the membrane flux and fouling resistance. Overall, we report an easy fabrication method of efficient nanocomposite zwitterionic ultrafilter membranes for water treatment with excellent flux, protein separation, filtration efficiency, and antifouling behavior. Graphical abstract: Image 1 Highlights: Synthesis of zwitterionic silica nanogels and nanocomposite membrane. Simultaneous sol-gel reaction of zwitterionic silane and phase inversion of membrane. Formation of highly dispersed zwitterionic silica nanogels in the membrane matrix. Enhanced antifouling, flux, rejection, and recovery properties of membranes.